Tropical cyclones over the South China Sea suppress the monsoonal rainfall in southern China - Xinyu Li; Riyu Lu; Guixing Chen; Ruidan Chen (npj Climate and Atmospheric Science, 2023)
Abstract The tropical cyclones (TCs) often cause intense rain and destructive winds. While these catastrophic weather conditions capture our attention, the less-known impact of TCs remains overlooked. This study reveals that TCs have a notable suppressive effect on monsoonal rainfall in southern China when they traverse the South China Sea. This phenomenon can be attributed to the influence of these mesoscale disturbances on the quasi-stationary, large-scale monsoonal circulation, which alters the moisture pathway. Furthermore, the case-by-case analysis indicates that ~76% of TCs correspond to rainfall reduction, whereas the other 24% correspond to rainfall increase. The latter is due to the concurrent occurrence of another independent influencing factor: extratropical cyclonic anomalies that promote enhanced rainfall through favoring lower-tropospheric moisture convergence. This study suggests that TCs, as mesoscale disturbances, can change the moisture channel that is usually controlled by quasi-stationary and large-scale monsoonal airflows, and suppress the adjacent land rainfall over China.